JOURNAL OF GOVERNMENT & POLITICS : The Line of Fit towards ASEAN Connectivity: Focus on the Philippine Political Structure and Processes - Hilton J. Aguja (FISIPOL UMY, 2016)
The hanoi Declaration on the adoption of the Master Plan on ASEAN Connectivity was adopted on 28 October 2010.